Circulating androgen levels before and after oophorectomy in premenopausal and postmenopausal women. (4th March 2019) - Stanczyk, F. Z.; Chaikittisilpa, S.; Sriprasert, I.; Rafatnia, A.; Nadadur, M.; Mishell, D. R.
Abstract: Objective: This study aimed to determine the effect of oophorectomy on baseline serum levels of androgens and estrogens in premenopausal and postmenopausal women. Methods: Fourteen premenopausal and 10 postmenopausal women underwent total hysterectomy and bilateral oophorectomy for benign disease of the uterus. Serum levels of dehydroepiandrosterone sulfate (DHEAS), androstenedione (A), testosterone (T), dihydrotestosterone (DHT), 5α-androstane-3α, 17β-diol-17β-glucuronide (3α-diol G), estrone (E1 ), estradiol (E2 ), and sex hormone-binding globulin (SHBG) were measured by highly specific immunoassays prior to surgery and 2 weeks afterward. Free T and free E2 were calculated. Differences were determined between preoperative (preop) and postoperative (postop) samples, and between premenopausal and postmenopausal women. Results: In premenopausal women, postop levels of total and free T, DHT, and total and free E2 decreased significantly from preop. Postop levels of DHEAS, A, 3α-diol G, and SHBG were decreased, but not significantly different from preop. In postmenopausal women, postop levels of total and free T and total and free E2 decreased significantly from preop, but there was little change in the other compounds. Significant differences in the mean change from baseline between premenopausal and postmenopausal women were observed only for E1 and total and free E2 . Conclusion: The significant decrease in serum T in postmenopausal women following oophorectomy adds to the evidence that the postmenopausal ovary continues to produce T.